2015
DOI: 10.2527/jas.2014-7912
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a new 6-phytase obtained from Buttiauxella spp. expressed in Trichoderma reesei on digestibility of amino acids, energy, and nutrients in pigs fed a diet based on corn, soybean meal, wheat middlings, and corn distillers' dried grains with solubles

Abstract: Sixteen cannulated pigs were used to evaluate the effect of a new 6-phytase derived from Buttiauxella spp. and expressed in Trichoderma reesei on apparent ileal digestibility (AID) of AA and apparent total tract digestibility (ATTD) of DM, N, Ca, P, Na, Mg, K, Cl, and energy. Pigs were fed 4 diets for 2 periods in a crossover design. Within each period, there were 4 blocks of 4 pigs per block with each diet represented within each block. The average initial BW in periods 1 and 2 were 22 and 30 kg, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 24 publications
8
25
3
Order By: Relevance
“…1000 FTU/kg) continued to increase the digestibility of P and amino acids (Adedokun et al 2015), indicating both phosphoric and extra-phosphoric effects. Additionally, Remus et al (2015) observed that increasing Buttiauxella phytase dose from 500 to 1000 FTU/kg further improved production performance of growing pigs fed corn and soybean meal based diets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1000 FTU/kg) continued to increase the digestibility of P and amino acids (Adedokun et al 2015), indicating both phosphoric and extra-phosphoric effects. Additionally, Remus et al (2015) observed that increasing Buttiauxella phytase dose from 500 to 1000 FTU/kg further improved production performance of growing pigs fed corn and soybean meal based diets.…”
Section: Introductionmentioning
confidence: 99%
“…Thus increasing phytase dose from 500 to 1000 FTU/ kg in grower pigs weighing 30 to 85 kg BW can result in additional economic benefits. Furthermore, using high dose phytase can further increase P digestibility and reduce P excretion, providing an environmental benefit (Adedokun et al 2015;Bento et al, 2012).…”
Section: Journal Of Applied Animal Nutritionmentioning
confidence: 99%
“…2 No data available for cells containing "-". ◊ ity over and above the expected improvements in P and Ca (Adedokun et al, 2015;Zeng et al, 2015), and this, combined with the differential pH optimum of Buttiauxella sp. phytase, which allows for nutrient release higher in the digestive tract (Menezes-Blackburn et al, 2015), will contribute to the reduction in weight loss demonstrated in this study.…”
Section: Discussionmentioning
confidence: 92%
“…In weaned piglets, it has previously been reported that supplementation of an E. coli phytase increased ADG, apparent ileal digestibility of CP and amino acids compared with pigs fed a NC diet ( Yáñez et al., 2013 ). In other studies, using Buttiauxella phytase, it has been reported that supplementation with this enzyme improved energy and amino acids digestibility in piglets ( Zeng et al., 2015 ), grower pigs ( Adedokun et al., 2015 , Lizardo et al., 2015 ) and in broilers ( Amerah et al., 2014 ). Amerah et al.…”
Section: Discussionmentioning
confidence: 95%